Leveraging Mobile Therapy Systems for Competitive Advantage in Depression Treatment Among Mental Health Counsellors in Enugu State, Nigeria - Otu, Mkpoikanke (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Depression remains a significant global health challenge, particularly in low- and middle-income countries where access to mental health care is limited. Mobile Therapy Systems (MTS) offer an innovative approach to addressing these challenges. This study examined the use, effectiveness, and challenges associated with MTS for depression treatment among mental health counsellors in Enugu State, Nigeria. Using a binomial test, data were analyzed from 34 counsellors to identify patterns in MTS adoption, preferred features, and barriers to usage. The findings revealed that 70.6% of counsellors reported using MTS, with occasional use being the most common (58.8%). Social media platforms like WhatsApp and Facebook were the most utilized, while features such as cognitive-behavioral therapy modules and data privacy were rated as essential. Customization of MTS to local contexts and cultural needs was deemed "very important" by 73.5% of respondents. Despite its potential, counsellors identified technical issues, high costs, and limited client acceptance as significant barriers to MTS adoption. This study highlights the importance of user-friendly, affordable, and culturally adaptive MTS platforms in expanding access to mental health care. Recommendations include improving digital infrastructure, providing targeted training for counsellors, and fostering public awareness to enhance client acceptance. The findings offer actionable insights for optimizing MTS implementation in resource-limited settings, contributing to the broader discourse on digital health innovations in mental health care.